Dissecting the nucleotide binding properties of the septins from S. cerevisiae. Issue 1 (15th November 2018) - Baur, Julian David; Rösler, Reinhild; Wiese, Sebastian; Johnsson, Nils; Gronemeyer, Thomas
Abstract: Septins are a conserved family of guanosine triphosphate (GTP)‐binding proteins that assemble into an ordered array of filaments at the mother bud neck in Saccharomyces cerevisiae cells. They are present in all higher eukaryotes except plants. Septins belong structurally to the P‐Loop nucleoside triphosphatase (NTPases) like Rab and Ras. However, unlike other small guanosine triphosphatase (GTPases) septins are supposed to act as scaffolds rather than signalling mediators. This is why they are considered as the fourth class of cytoskeletal proteins. It is assumed that septins fulfil their functions independently of the bound nucleotide. The role of guanosine diphosphosphate (GDP) and GTP binding and subsequent hydrolysis was controversial debated in the last couple of years. Lack of crystal structures of yeast septin subunits or rods and difficulties to isolate single monomeric septin subunits often hindered the correlation of results obtained from in vivo studies with biochemical data. Recently, nucleotide binding and hydrolysis was connected to the formation of septin rods from its subunits. However, the evidence was only indirectly obtained through the use of septin mutants in the context of intact cells. We provide here mechanistic insight into the nucleotide binding of the yeast septins by in vitro assays using purified septin rods and building blocks, thereby adding further insights to the already available models on septin filament formation.